2023
DOI: 10.1681/asn.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 2α Attenuates Renal Ischemia-Reperfusion Injury by Suppressing CD36-Mediated Lipid Accumulation in Dendritic Cells in a Mouse Model

Abstract: Background Hypoxia and hypoxia-inducible factors (HIFs) play essential and multiple roles in renal ischemia-reperfusion injury (IRI). Dendritic cells (DCs) comprise a major subpopulation of the immunocytes in the kidney and are key initiators and effectors of the innate immune responses after IRI. The role of HIF-2a in DCs remains unclear in the context of renal IRI.Methods To investigate the importance of HIF-2a in DCs upon renal IRI, we examined the effects of DC-specific HIF-2a ablation in a murine model. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that DC activation in RIRI is accompanied by an increase in HIF-1a protein levels, and knockdown of HIF-1a significantly inhibits DC maturation and impairs the stimulation of allogeneic T cells (80, 81). In contrast, a recent study showed that HIF-2a deficiency in DCs upregulated CD36 expression in DCs, leading to cellular lipid accumulation, causing the overactivation of natural killer T (NKT) cells the production of IFN-g and IL4, and ultimately exacerbating RIRI in mice (82). This finding suggests that hypoxia plays a crucial role in DC activation, and targeting and regulating HIF-1a or HIF-2a expression could be a potential therapeutic strategy for RIRI.…”
Section: Renal Ischaemia-reperfusion Injury (Riri)mentioning
confidence: 94%
“…Previous studies have shown that DC activation in RIRI is accompanied by an increase in HIF-1a protein levels, and knockdown of HIF-1a significantly inhibits DC maturation and impairs the stimulation of allogeneic T cells (80, 81). In contrast, a recent study showed that HIF-2a deficiency in DCs upregulated CD36 expression in DCs, leading to cellular lipid accumulation, causing the overactivation of natural killer T (NKT) cells the production of IFN-g and IL4, and ultimately exacerbating RIRI in mice (82). This finding suggests that hypoxia plays a crucial role in DC activation, and targeting and regulating HIF-1a or HIF-2a expression could be a potential therapeutic strategy for RIRI.…”
Section: Renal Ischaemia-reperfusion Injury (Riri)mentioning
confidence: 94%